High Rate Capability of Lithium Chromium Titanium Oxide Hierarchical Mesoporous Microspheres Anode Materials Synthesized by a One-Pot Co-Precipitation for Lithium Ion Batteries. Issue 9 (9th July 2016) - Zhang, Ping; Huang, Yudai; Jia, Wei; Cai, Yanjun; Wang, Xingchao; Guo, Yong; Jia, Dianzeng; Sun, Zhipeng; Wang, Ruiying; Tang, Xincun; Wang, Lishi
Abstract : Li4-x/3 Ti5-2x/3 Crx O12 hierarchical mesoporous microspheres have been synthesized by a one-pot co-precipitation method. The crystal structures, morphologies and electrochemical performances of the as-prepared materials were analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), electron microscopy and electrochemical testing. The XRD results show that the materials are pure phase and perfect crystalline with spinel structure. XPS results further identify the chemical state of Cr is trivalent, Ti is trivalent and tetravalent in Li3.85 Ti4.70 Cr0.46 O12 . Microscopic observations reveal that Li3.85 Ti4.70 Cr0.46 O12 shows hierarchical mesoporous microsphere structure. Li3.85 Ti4.70 Cr0.46 O12 exhibits excellent electrochemical properties, the rate capacity reaches 192.7 mAh g −1, 182.6 mAh g −1, 179.0 mAh g −1, 172.2 mAh g −1 and 163.9 mAh g −1 at 0.5 C, 1 C, 2 C, 5 C and 10 C, respectively. The discharge capacity of 152.9 mAh g −1 can be obtained after 200 cycles at 10 C. Furthermore, Cr-doping not only reduces polarization, but also increases Li + diffusion rate of the material.